Comparative assessment of the area of sealer voids in single cone obturation done with mineral trioxide aggregate, epoxy resin, and zinc-oxide eugenol based sealers - Anisha Kumar; A R Vivekananda Pai (Wolters Kluwer Medknow Publications, 2016)
Introduction: Voids in the sealer mass have the potential to allow leakage through obturation. They are more critical in single cone (SC) obturation as the volume of sealer used in this obturation is larger when compared to other obturations. Aim: To compare the area of voids in mineral trioxide aggregate (MTA)-based, resin-based, and zinc oxide-eugenol-based sealers when employed with SC obturation technique. Materials and Methods: Fifteen teeth were cleaned and shaped and divided into three groups for SC obturation using MTA Fillapex, AH26, and Pulpdent sealers, respectively. The obturated teeth were sectioned at apical, middle, and coronal third, and area of voids in the sealer was assessed using a stereomicroscope and digital images and image software. The results were statistically analyzed using SPSS software and Kruskal-Wallis and Mann-Whitney tests. Results: The three tested sealers showed voids in all the sections except MTA Fillapex, which was void free in apical and middle sections. There were significant differences between these sealers regarding their section wise area of voids (P < 0.05). Similarly, there were significant differences in their overall area of voids (P < 0.05) with MTA Fillapex showing significantly least area of voids followed by AH26. Conclusions: SC obturation with MTA Fillapex sealer, which showed void free apical and middle third sections, had significantly least area of voids in the sealer followed by the one with AH26 sealer, whereas SC obturation with Pulpdent sealer had significantly most area of voids.